2021
DOI: 10.1177/08901171211038545
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Purpose in Life and Subsequent Physical, Behavioral, and Psychosocial Health: An Outcome-Wide Approach

Abstract: Purpose: Growing evidence indicates that a higher sense of purpose in life ( purpose) is associated with reduced risk of chronic diseases and mortality. However, epidemiological studies have not evaluated if change in purpose is associated with subsequent health and well-being outcomes. Design: We evaluated if positive change in purpose (between t0; 2006/2008 and t1;2010/2012) was associated with better outcomes on 35 indicators of physical health, health behaviors, and psychosocial well-being (at t2;2014/2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 59 publications
6
42
1
3
Order By: Relevance
“…These results are novel since they relate the cognitive reserve to motivational reserve and specifically to the meaning of life. They extend and converge with many studies that relate the meaning of life with positive neuropsychological aspects such as less anxiety and depression, greater physical, psychological and social well-being, as well as greater life expectancy and optimism ( Park et al, 2004 ; Peterson and Seligman, 2004 ; Kim et al, 2013 ; Proyer et al, 2013 ; Niemiec, 2014 ; Zilioli et al, 2015 ; Cohen et al, 2016 ; Steptoe, 2019 ; Steptoe and Fancourt, 2019 ; Trudel-Fitzgerald et al, 2019 ; Kim et al, 2020 ; Weziak-Bialowolska et al, 2021 ; Kim et al, 2022 ).All these variables can be related by key factors such as positive emotions, which are directly related to these constructs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These results are novel since they relate the cognitive reserve to motivational reserve and specifically to the meaning of life. They extend and converge with many studies that relate the meaning of life with positive neuropsychological aspects such as less anxiety and depression, greater physical, psychological and social well-being, as well as greater life expectancy and optimism ( Park et al, 2004 ; Peterson and Seligman, 2004 ; Kim et al, 2013 ; Proyer et al, 2013 ; Niemiec, 2014 ; Zilioli et al, 2015 ; Cohen et al, 2016 ; Steptoe, 2019 ; Steptoe and Fancourt, 2019 ; Trudel-Fitzgerald et al, 2019 ; Kim et al, 2020 ; Weziak-Bialowolska et al, 2021 ; Kim et al, 2022 ).All these variables can be related by key factors such as positive emotions, which are directly related to these constructs.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, we also have to consider the positive effects and all the human strengths as part of the motivational aspects ( Reich et al, 2004 ) that have been appropriate and developed, among which is worth highlighting the values and vital goals ( Park et al, 2004 ; Peterson and Seligman, 2004 ). In older people, numerous studies have shown that having a better perspective on one’s own meaning of life is related to better psychosocial health, physical well-being, a lower risk of mortality and depression, less loneliness, more optimism and more allostatic load ( Zilioli et al, 2015 ; Cohen et al, 2016 ; Steptoe and Fancourt, 2019 ; Kim et al, 2020 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, identifying factors that contribute to healthy trajectories of mental and physical health, and also counteract despair, is vital for improving the health and well-being of older adults ( Oppers et al, 2012 ). While much effort has focused on identifying risk factors of disease, investigators are increasingly seeking potentially modifiable health assets that uniquely enhance a person's ability to foster healthy behaviors and physical health ( Kim et al, 2021 ; Kubzansky et al, 2018 ; Levine et al, 2021 ; Ryff, 2014 ; VanderWeele, 2017 ; VanderWeele et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have shown that a strong sense of purpose in life is central to leading an active life, and that a lack of purpose in life can lead to boredom, increase risk of depression, and diminish resilience. Although only a few studies have assessed the pathophysiological outcomes of lack of purpose, a large number of recent studies have shown that lack of purpose increases the risk of death [38].…”
Section: Lack Of Sense Of Purposementioning
confidence: 99%